Problematika Yuridis Pemungutan Suara Ulang dalam Pemilihan Kepala Desa - Mansur Mansur; Ahmad Rustan; Irwansyah Irwansyah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Pemungutan suara ulang (PSU) in the election of village heads has not been expressly regulated in Law Number 6 of 2014 concerning Villages and its implementing regulations, thus causing legal uncertainty and differences in practices between regions. This study aims to analyze the legal basis, authority, and juridical implications of PSU in the election of village heads. The research method used is normative juridical with a legislative approach. The results of the study show that the lack of regulation and weak operational guidelines expand the discretion of the Regent/Mayor and potentially affect the legitimacy of the results of the village head election. Therefore, special arrangements are needed that contain PSU procedures in a clear, uniform, and measurable manner to ensure legal certainty and the integrity of village democracy.